1980
DOI: 10.1093/oxfordjournals.aje.a112886
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Cancer and Occupation: A Case-Control Study1

Abstract: In reviews of malignancy and occupation, cancer of the nose and paranasal sinuses (sinonasal cancer (SNC) is frequently mentioned. In a case-control study of SNC among subjects who died in Connecticut in the period 1935--1975, occupations from death certificates and city directories were compared to job titles taken from previous literature. The results do not support an association of the cancer with nickel (odds ratio = 0.7, 95% confidence limits (CL): 0.4, 1.5) but do support an association with cutting oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 0 publications
1
23
1
2
Order By: Relevance
“…As described in Hoppin et al [1998], while chlorophenolic biocides are known to have been used in some cutting oils, the prevalence of their use, as well as changes in their pattern of use over time, are unclear. One previous study reported an association between occupational exposure to cutting oils and sinonasal cancer [Roush et al, 1980]. The results of the current analysis support the association reported by Roush et al, and suggest that further work should seek to establish whether chlorophenols in cutting oils, some other constituent of cutting oils, or another aspect of machining is etiologically linked to nasal and nasopharyngeal cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As described in Hoppin et al [1998], while chlorophenolic biocides are known to have been used in some cutting oils, the prevalence of their use, as well as changes in their pattern of use over time, are unclear. One previous study reported an association between occupational exposure to cutting oils and sinonasal cancer [Roush et al, 1980]. The results of the current analysis support the association reported by Roush et al, and suggest that further work should seek to establish whether chlorophenols in cutting oils, some other constituent of cutting oils, or another aspect of machining is etiologically linked to nasal and nasopharyngeal cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Work in wood-related occupations has been reported to be associated with nasal and nasopharyngeal cancers [Acheson et al, 1967;Brinton et al, 1977;Roush et al, 1980;Elwood, 1981;Brinton et al, 1984;Vaughan and Davis, 1991;Sriamporn et al, 1992]. Chlorophenols, used as wood preservatives, are one of the suspected exposures within wood-related occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Because of t h e low incidence of nasal cancers, the case-referent approach proved to b e suitable t o test the association of this disease with occupational exposures in t h e wood and furniture industry (4,5,8,11,13), given that t h e proportion of exposed people i n t h e population under study were not too low.…”
mentioning
confidence: 99%
“…The previous study did not include a house carpenter but in the present study, occupation I, which was construction workers including house carpenters seemed to positively correlate with the cancer mortality. The construction workers or house carpenters have been reported to be a risk occupation for the maxillary sinuses cancer (Acheson, 1972;Milham, 1974;Ironside, 1975;Roush, 1980 …”
Section: Discussionmentioning
confidence: 99%